Comprehensive in vivo and in vitro metabolic profiling of amphenmulin: a novel pleuromutilin derivative characterized by UHPLC-Q-TOF-MS/MS - Wang, Wenxiang; Wang, Luoju; Deng, Qin; Su, Dehai; Tang, Youzhi; Ding, Huanzhong (Frontiers in Veterinary Science, 2025)
Amphenmulin is a novel pleuromutilin derivative with proven excellent antibacterial activity. To investigate its metabolism in animals, ultra-high-performance liquid chromatography coupled with quadrupole/time-of-flight mass spectrometry (UHPLC-Q-TOF-MS/MS) was employed to analyze and identify in vivo metabolites in rats and chickens and in vitro using human, rat, pig, chicken and beagle dog liver microsomes. We identified 18 metabolites from liver microsomes and 24 and 17 in vivo metabolites for rats and chickens, respectively. The primary amphenmulin metabolic pathways involved sulfur oxidation of the side chain, hydroxylations on the aniline moiety and the parent mutilin nucleus, and the primary in vivo metabolites in rats and chickens were amphenmulin-sulfoxide (M2) and hydroxy-amphenmulin (M1). These findings provide a structural basis for further investigation into the pharmacokinetics and safety profile of amphenmulin and serve as a reference for the development and optimization of other pleuromutilin derivatives.